2016
DOI: 10.1007/s10482-016-0808-0
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of vanadate monomer with the mycelium of fungus Phycomyces blakesleeanus: reduction or uptake?

Abstract: The possibility of reduction of vanadate monomer in the mycelium of fungus Phycomyces blakesleeanus was investigated in this study by means of polarography. Control experiments were performed with vanadyl [V(IV)] and vanadate [V(V)] in 10 mM Hepes, pH 7.2. Addition of P. blakesleeanus mycelium resulted in disappearance of all V(IV) polarographic waves recorded in the control. This points to the uptake of all available V(IV) by the mycelium, up to 185 µmol/g, and suggests P. blakesleeanus as a potential agent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Alternatively, these observations are consistent with a hydrophobic environment having been reported in some cases to alter composition and speciation and impact the shifting of observed signals. Combined, these studies showed convincingly that the cell wall is not responsible for reduction of vanadate (Hadzibrahimovic et al, 2017 ) and these studies also confirm that tetrameric vanadate is not able to enter the cells (Zizic et al, 2016 ) as reported in yeast as well (Crans et al, 2002 ) (Willsky et al, 1984a , b .)…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Alternatively, these observations are consistent with a hydrophobic environment having been reported in some cases to alter composition and speciation and impact the shifting of observed signals. Combined, these studies showed convincingly that the cell wall is not responsible for reduction of vanadate (Hadzibrahimovic et al, 2017 ) and these studies also confirm that tetrameric vanadate is not able to enter the cells (Zizic et al, 2016 ) as reported in yeast as well (Crans et al, 2002 ) (Willsky et al, 1984a , b .)…”
Section: Discussionmentioning
confidence: 58%
“…These studies were very elegant and truly important, because they documented the formation of decavanadate in cells from monomeric vanadate for the first time (Willsky et al, 1984b ). Recently, Zakrzewska and Zivic reported a series of studies in fungi exploring the uptake of both vanadate and V(IV) using 51 V and EPR spectroscopy, as well as polarographic studies (Zizic et al, 2013 , 2016 ; Hadzibrahimovic et al, 2017 ). The initial 51 V NMR studies on Phycomyce blakesleeanus mycelium were supplemented with polarography, which allowed for the assignment of the signal at −535 ppm accumulating inside the fungi cells to V 1 even though the pH of the system was defined by HEPES buffer at 7.2 where V 1 generally has a peak position at a higher frequency (Zizic et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%